Surface modification of activated carbon via hcl or nh4 oh treatment to enhance the removal of cr(Vi) from aqueous solution - Ferrer, Marleane Rovi Ramos; Kang, Jin Kyu; Choi, Jae Woo; Lee, Chang Gu; Park, Seong Jik (Desalination and Water Treatment, 2021)
Surface-modified activated carbon (AC) was fabricated using different concentration of HCl or NH4 OH to enhance its adsorption capacity for the removal of Cr(VI) from aqueous solution. Surface-modified ACs were also characterized by analyzing their morphologies, specific surface area, zeta potential, elemental composition, and functional groups. Batch adsorption experiments revealed that the modification of AC with HCl was more effective for increasing Cr(VI) removal by AC than NH4 OH. Cr(VI) adsorption onto AC treated with 20% HCl (20H-AC) under different contact times followed the pseudo-second-order model, indicating that chemisorption limited the rate of Cr(VI) adsorption. The determination coefficient of the Langmuir model fit was higher than that of the Freundlich model. The maximum adsorption capacity of 20H-AC for Cr(VI) was 177.9 mg/g, which was comparable to adsorbents listed in other literatures. A thermodynamic study showed that Cr(VI) adsorption onto 20H-AC is an endothermic and spontaneous reaction and chemisorption. An increase in solution pH from 2 to 10 resulted in a significant decrease in – the adsorption amount of Cr(VI), that is from 78.37 to 28.40 mg/g. The negative influence of HCO3 2– on the Cr(VI) adsorption was higher than that of SO4 and NO3– . Therefore, this study reveals that the modification of AC using HCl is effective in enhancing the removal efficiency of Cr(VI).
Keywords: Acid treatment; Activated carbon; Base treatment; Cr(VI) removal; Surface-modification